Patente canvas: transformando a maneira de criar patentes inovadoras - Ferreira, Fernando Kobuti [UNIFESP] (2016)
Inspired by the well-known and renowned " canvas " of the book Business Model Canvas Alexander Osterwalder & Yves Pigneur , Patent Canvas is a tool to assist in the planning and creation of innovative patents. Patent Canvas covers the main points that are essential to understand and evaluate the potential of any patent. It is a pre formatted visual map containing eleven business model blocks of an innovative patent. It allows relating information in a systemic , integrated and quickly. Patent Canvas is useful to discuss and integrate insights on how the patent creates value . Patent Canvas is available through an e-book that can be accessed at patentecanvas.com .